PROBLEMATIKA IMPLEMENTASI E-SERTIFIKAT PERTANAHAN DI KALIMANTAN TIMUR - Andri Pranata; Tajuddin (INTELIGENSIA MEDIA, 2025)
The implementation of E-Certificate of Land in East Kalimantan has brought significant changes to land administration systems, aiming to improve efficiency, security, and accessibility of services. Previously, the manual process of obtaining land certificates was time-consuming and involved complex bureaucracy, which made it difficult for the public. With digitalization, the process of obtaining certificates has become faster, safer, and more efficient, while reducing the risk of forgery or loss of certificates. People can now access land services online without having to visit the land office, thus increasing transparency and reducing dependence on intermediaries or third parties. However, the implementation of E-Certificates also faces various challenges, particularly related to inadequate technology infrastructure, limited internet access in rural areas, and the readiness of technology in land offices. Additionally, low digital literacy among the public and insufficient socialization and education about the benefits of the digital system hinder wider adoption. Legal challenges regarding the uncertainty of the validity of E- Certificates in land dispute resolution also pose issues that need to be addressed. Overall, despite these challenges, the implementation of E-Certificates in East Kalimantan holds significant potential to improve land administration efficiency, expedite the land certification process, and open up broader investment opportunities. Efforts to improve technology infrastructure, increase digital literacy, and refine legal regulations will help ensure the successful implementation of this system and provide maximum benefits to the people of East Kalimantan